Distribution of Large Wood Within River Corridors in Relation to Flow Regime in the Semiarid Western US. Issue 3 (15th March 2018) - Wohl, Ellen; Cadol, Daniel; Pfeiffer, Andrew; Jackson, Karen; Laurel, DeAnna
Abstract: The cumulative volume and spatial distribution of large wood (LW) along river corridors (channels and floodplains) reflect interactions between rates and volumes of LW recruitment and channel transport capacity through time. Rivers of the semiarid interior western US can have relatively low‐magnitude disturbances associated with annual snowmelt or relatively high‐magnitude disturbances associated with episodic rainfall runoff, especially following wildfires. We use characteristics of LW from 25 river segments in four regions of New Mexico and Colorado to analyze wood loads and spatial patterns of wood distribution in relation to disturbance regime. High‐magnitude disturbances move LW onto floodplains and create longitudinally nonuniform LW distributions with aggregated (closer together than random) LW pieces and abundant LW jams in the floodplain. Sites with low‐magnitude disturbances have a greater proportion of LW in the channel and much of this wood is within segregated (farther apart than random) jams. These results imply that river management, which typically focuses on LW within channels, should focus on floodplain as well as in‐channel LW in rivers with high‐magnitude disturbances. The results also indicate that the proportions of LW loads in channels versus floodplains can differ significantly among rivers with different disturbance regimes that are otherwise similar in terms of forest type or drainage area. This is particularly relevant to mountainous regions with elevation‐related changes in flow and disturbance regime. River management that reintroduces LW to river corridors will be most effective if it incorporates the mobility and spatial distribution of LW. Key Points: Distribution of large wood in a river corridor reflects disturbance regime defined via magnitude of floods High magnitude disturbances in sparsely wooded river corridors redistribute wood onto floodplains Low magnitude disturbances result in wood distributed primarily within the active channel